Analisis Peran Guru Pada Sekolah Dengan Program Student LED Conference Dalam Pengembangan Karakter Siswa (Studi Kasus Mi Progresif Al Musthofa Bangsal): Analysis of the Role of Teachers in Schools with Programs Student LED Conference in Student Character Development (Case Study of Al Musthofa Bangsal Progressive Ibtidaiyah Madrasah) - Ainun Nurasiah; Yhasinta Agustyarini; DWI HASANAH, KARTINI (PT. Intelek Cendikiawan Nusantara, 2024)
Abstract The Student LED Conference program has become an innovative approach in education that places students as the main leaders in evaluating their own progress. In the context of student character development, the role of the teacher has a significant impact. The aim of this research is to analyze the role of teachers in schools with the Student LED Conference program in developing student character, describing the supporting and inhibiting factors in the role of teachers in schools with the Student LED Conference program in developing student character at MI Progressive Al Musthofa Bangsal. This research uses a qualitative approach, a case study type of research. The data collection techniques used were interviews, observation and documentation, then analyzed by reducing the data, presenting the data and drawing conclusions. The research results show that the role of teachers in schools with the Student LED Conference program in developing student character is very important. Research shows that teachers act as facilitators, mentors and evaluators. The supporting factor is that students and parents can be invited to collaborate in the process of implementing the Student LED Conference. The inhibiting factor is if student attendance is irregular or inconsistent. Keywords : Teacher's Role, Student LED Conference, Student character